2020
DOI: 10.1007/s00029-019-0534-3
|View full text |Cite
|
Sign up to set email alerts
|

Meromorphic continuation of Selberg zeta functions with twists having non-expanding cusp monodromy

Abstract: We initiate the study of Selberg zeta functions Z Γ,χ for geometrically finite Fuchsian groups Γ and finite-dimensional representations χ with non-expanding cusp monodromy. We show that for all choices of (Γ, χ), the Selberg zeta function Z Γ,χ converges on some half-plane in C. In addition, under the assumption that Γ admits a strict transfer operator approach, we show that Z Γ,χ extends meromorphically to all of C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…By the Venkov-Zograf factorization formula [26,25] (see also Fedosova-Pohl [6] for the infinite-area case), the Selberg zeta function of any finite-index subgroup Γ of Γ w equals the Selberg zeta function of Γ w twisted with the representation of Γ w that is induced by the trivial one-dimensional representation of Γ. This allows us to deduce the following corollaries of Theorem 1.1.…”
Section: Introduction and Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…By the Venkov-Zograf factorization formula [26,25] (see also Fedosova-Pohl [6] for the infinite-area case), the Selberg zeta function of any finite-index subgroup Γ of Γ w equals the Selberg zeta function of Γ w twisted with the representation of Γ w that is induced by the trivial one-dimensional representation of Γ. This allows us to deduce the following corollaries of Theorem 1.1.…”
Section: Introduction and Resultsmentioning
confidence: 88%
“…For example, we may consider the subgroup of index 2 which is freely generated by the elements T w and ST w S, as well as its abelian covers. It extends meromorphically to all of C. The set of poles is contained in 1 2 (1 − N 0 ), and bounds on the order of poles can be given [21,6].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…For any Fuchsian group Γ with parabolic elements, the class of representations with non-expanding cusp monodromy is a proper superset of those which are only unitary at cusps. We refer to [7,Section 5] for examples of representations with nonexpanding cusp monodromy that are not unitary at cusps. Throughout the last few decades, representations with non-expanding cusp monodromy have already been seen to be of huge interest.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], we established, for any geometrically finite Fuchsian group Γ, convergence of the Selberg zeta functions for Γ with twists of non-expanding cusp monodromy. We further showed that for a certain rather large subclass of Fuchsian groups these Selberg zeta functions have a meromorphic continuation to all of C. Moreover, we proved that for twists without non-expanding cusp monodromy, the twisted Euler products used for the definition of Selberg zeta functions do not converge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation